Current Stem-Cell Approaches for the Treatment of Inherited Retinal Degenerations. (19th May 2019) - Terrell, David; Comander, Jason
ABSTRACT: Stem cells provide a promising new therapeutic approach for the treatment of multiple acquired and inherited retinal conditions. While to date, there have been numerous clinical trials examining the ability of stem cells to treat the geographic atrophy found in advanced non-neovascular age-related macular degeneration, fewer clinical trials have specifically examined stem-cell therapy for inherited retinal disease. Moreover, it remains to be seen if human stem cells will be able to regenerate the lost retinal cell populations that represent a final common pathway for most of the inherited retinal diseases, or if stem cells will secrete a neuroprotective paracrine factor that will delay progression of these diseases. Here, we will review a number of the current clinical trials, either completed or in process, that have been designed to specifically treat inherited retinal conditions. There was considerable initial concern that using human stem cells as therapeutic agents might have the potential to form benign tumors or trigger an immune response that would have deleterious effects on the patient's retina. Currently, the majority of the clinical trials reviewed share the conclusion that intraocular stem-cell approach is generally well tolerated and safe for patients. While there are some efficacy data that have been published for a few of the reviewed trials, none of the completed studies have been empowered to demonstrate statistically significant efficacy in humans.